(untitled) (GEOmedia, 2016)
PAROLE CHIAVE Cartografia geologica; Storia della geologia; Geologia urbana; Roma ABSTRACT Geological mapping is one of the most innovative "discoveries" (in Earth Sciences development) of the 19th century and it represented the basic knowledge for the economic exploitation of many European countries. In 1873, with the foundation of the Regio Ufficio Geologico, started the systematic geological survey of the Italian territory and its cartographic representation. In the previous period some scientists reported on scientific publications the results of their studies and surveys carried out in different parts of the peninsula. Undoubtedly, the early example is the "Geological scheme of Rome”, realized by Giovanni Battista Brocchi between 1820 and 1830. The analysis of scientific and cartographic production carried out by several authors in the urban area of Rome and its surroundings permitted us to built a Story telling project finalized to highlight the progress of geological knowledge, placing the individual works in the historical and cultural context of the period. This reconstruction path is done by exploiting the potential of ESRI ArcGIS Online tools, with the purpose of enhancing the scientific and cultural content of the geological cartography contributing to the knowledge of Geological Sciences development.